Effectiveness of environmentally safe products «VetOks-1000», «Sumerian silver» for the prevention of pseudomonosis of poultry embryos associated with bacteriosis - Berezovskiy, Andriy; Fotina, Tetiana; Vashchyk, Yevheniia; Bobrytska, Olga; Seliukova, Nataliia; Shtrygol’, Sergiy; Zakhariev, Andriy; Dubin, Ruslan (ScienceRise: Biological Science, 2023)
The aim: study of the effectiveness of environmentally safe means «Vetoks-1000», «Sumerian silver» for the prevention of pseudomonosis of poultry embryos, associated with bacteriosis. Materials and methods. The effectiveness of the preparations «VetOks-1000», «Sumerian silver» in relation to E. coli, P. aeruginos, S. aureus, S. typhimurium was determined by the method of researching antimicrobial activity on test objects: galvanized iron, wooden bars (painted and unpainted), red brick and plaster cut-outs, 10 x 10 cm, and a hatching egg. The effectiveness of «VetOks-1000», «Sumerian silver» solutions compared to formaldehyde for disinfection of hatching eggs and incubation cabinets for the purpose of preventing pseudomonosis of poultry embryos was carried out in the production conditions of the hatchery, where P. aeruginosa, E. coli, S. аureus, were periodically isolated from asphyxiated embryos and from the carcasses of chicks of the first 10 days of life by comparing the hatching rate of chicks in the experimental and control groups. Results. It was established that the «Sumerian silver» had an antimicrobial effect against the causative agents of pseudomonosis and the main bacterioses of poultry in concentrations of 1–3 %, and the drug «VetOx-1000»was effective in concentrations of 0.024 %–0.03 % after exposure for 1-4 hours in depending on the type of surface. The number of conditioned young birds, obtained with the use of environmentally safe means «VetOks-1000», «Sumerian silver», was higher by (1.1-1.7) % compared to the number of young birds in the control group using formalin. Conclusions. The proposed method of prevention of associated pseudomonosis of poultry embryos by rotation of environmentally safe means in established bactericidal concentrations (3 % «Sumerian silver» solution and 0.03 % «VetOks 1000» solution) ensures a 1.1–1.7 % higher hatching of young birds compared to control using formalin